Prerequisites for implementing physical activity on prescription for children with obesity in paediatric health care: A cross-sectional survey - Boman, Charlotte; Bernhardsson, Susanne; Lauruschkus, Katarina; Lundqvist, Stefan; Melin, Karin (Frontiers in Health Services, 2023)
Background Physical inactivity is a main driver of childhood obesity that tracks into adulthood, making it crucial to address early in life. Swedish physical activity on prescription (PAP) is an effective intervention for increasing physical activity levels in adults and is being implemented in primary care in Sweden. Before implementing PAP for children, both intervention effectiveness and implementation prerequisites need to be examined. Framed by the Normalization Process Theory (NPT) domains, this study aimed to investigate perceptions of PAP amongst paediatric staff and managers working with children with obesity, as well as acceptability, appropriateness, feasibility, and barriers and facilitators for implementing PAP in paediatric health care. Methods Staff and managers in 28 paediatric outpatient clinics in western Sweden were surveyed using validated implementation instruments and open-ended questions. Data were analysed using Mann–Whitney U tests and Kruskal–Wallis tests. Qualitative data were categorised into NPT domains. Results The survey response rate was 54% (125/229). Most respondents (82%) reported PAP to be familiar and many (56%) perceived it as a normal part of work; nurses and physiotherapists to a greater extent (p < 0.001). This was anticipated to increase in the future (82%), especially amongst those with the longest work experience (p = 0.012). Respondents reported seeing the potential value in their work with PAP (77%), being open to working in new ways to use PAP (94%), and having confidence in their colleagues' ability to use PAP (77%). Barriers and facilitators were found in all the NPT domains, mainly collective action and reflexive monitoring, where, for example, inadequacies of education, resources, and research on PAP for children were reported as barriers. Most respondents agreed that PAP was acceptable, appropriate, and feasible (71% to 88%). Conclusions PAP is familiar and perceived as an acceptable, appropriate, and feasible intervention, and by many viewed as a normal part of clinical routines in paediatric outpatient clinics in western Sweden, especially by physiotherapists and nurses. Barriers and faciliators are mainly related to collective action and reflexive monitoring. The wide acceptance demonstrates receptiveness to PAP as an intervention to promote an active lifestyle for children with obesity.